Appearance of Verruca Over Nevus Unius Lateris – A Rare Occurrence of Locus Minoris Resistentiae - V Vijay; Manobalan Karunanandhan; Yogindher Singh (Clinical Dermatology Review)
Nevus unius lateris is an infrequent dermatological disorder which is characterized by verrucous epidermal nevus involving one half of the body. It is a variant of systematized epidermal nevus. It commonly displays an association with neurological, visual, auditory, and musculoskeletal involvement. Verruca are nonmalignant growths that manifest on the skin and mucous membranes. It is caused by the human papillomavirus. It characterized by warty growth over the skin. Here, we report a case of nevus unius lateris and appearance of verruca over nevus unius lateris in a 29-year-old male.